2014
DOI: 10.1073/pnas.1401695111
|View full text |Cite
|
Sign up to set email alerts
|

Major mouse placental compartments revealed by diffusion-weighted MRI, contrast-enhanced MRI, and fluorescence imaging

Abstract: Mammalian models, and mouse studies in particular, play a central role in our understanding of placental development. Magnetic resonance imaging (MRI) could be a valuable tool to further these studies, providing both structural and functional information. As fluid dynamics throughout the placenta are driven by a variety of flow and diffusion processes, diffusion-weighted MRI could enhance our understanding of the exchange properties of maternal and fetal blood pools-and thereby of placental function. These stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 37 publications
5
50
0
1
Order By: Relevance
“…This would support the oxygen reserve capacity of the placenta. Different regions within the placenta may be distinguished, according to the specific enhancements made in perfusion imaging and histological analyses [15]. Published studies have found no difference of oxygenation in these different areas [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…This would support the oxygen reserve capacity of the placenta. Different regions within the placenta may be distinguished, according to the specific enhancements made in perfusion imaging and histological analyses [15]. Published studies have found no difference of oxygenation in these different areas [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…This is conceivable since the thickness of interhemal membrane, which influences water diffusion between maternal and fetal blood spaces, also decreases with gestation [20, 55], leading to a theoretical increase in diffusion capacity (diffusion coefficient, D) with gestation [20]. Recent MR imaging based reports on the placental apparent diffusion coefficient (ADC), a measure of water diffusion in the whole placenta, however, showed no significant change with advancing gestation in both humans and mice [56, 57]. While these studies use relatively low resolution imaging and pertain to whole placental diffusion, a region-specific study of diffusion characteristics within the placenta, for example labyrinth vs. junctional, could help us in better observing their change trajectory as a function of gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several techniques could be combined to better understand placental physiologic condition, as reported in studies of placental blood flow in mice. 49 Further extensive experimental studies are required to better define the respective roles of each fMRI method in the functional assessment of the placenta and the optimal way in which ultrasound studies can be complimented. All fMRI techniques demonstrate a potential for allowing timely recognition of placental insufficiency, thus possibly allowing for appropriate planning for follow-up examinations and timing of delivery of high-risk fetuses.…”
Section: Commentmentioning
confidence: 99%